The impact of the appointment and qualification of independent directors on the performance of the company’s board - Mittal, Rachit (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to focus on frauds occurring in companies despite the appointment of independent directors. Despite various stringent laws, the concept of independent directors has come into the picture of corporations around the world following various scandals by the company’s board of directors. Legislative authorities are constantly revising their laws to prevent these frauds and protect the interests of minority shareholders, creditors and investors. The concept of an independent director is one of the major amendments to the respective regulatory bodies of different countries of the world. Here, in India it was firstly introduced in the late 90s and subsequently it had been added in the Listing Agreement under Clause 49. Later in 2015, SEBI (LODR) Regulations are introduced, where it has mentioned that the companies as prescribed under such regulations have to appoint an Independent Director.